Analisis Toko Pygmaeus Outdoor Sebagai UMKM Fashion Sepatu Outdoor - Rohmanulloh, Arif; Muhammad, Faisal; Winarno, Agung (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in driving regional economic growth, including in the fashion industry sector. This article reviews the Pygmaeus Outdoor fashion shoe MSME located in Mojokerto Regency. Pygmaeus Outdoor is a local business that markets various types of shoes targeting the youth segment with various activities. This review examines the business profile, business strategy, and the challenges and opportunities faced. This study uses a descriptive qualitative approach with a case study method. Data were collected through literature studies, social media searches, and customer review analysis. Researchers also conducted indirect interviews to explore Pygmaeus Outdoor's SWOT information. The results of the study show that Pygmaeus Outdoor has succeeded in building an image in the eyes of customers by offering original products at low prices through a digital marketing and market approach. This MSME is estimated to still have great potential to continue to grow by providing more outdoor fashion brands, providing more choices for the market, along with the massive increase in digital marketing. This article is also expected to provide insight into entrepreneurship learning and the importance of empowering local MSMEs based on added value.